PENGARUH KONEKSI POLITIK TERHADAP KINERJA LINGKUNGAN DAN PROFITABILITAS - Nofi Sulistyowati; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2020)
This study is to examine the effect of political connections on environmental performance and profitability. The variables used in this study are independent and dependent variables. Political connections as a independent variables. The dependent variable are environmental performance and profitability. The population in this study is companies listed on the Indonesia Stock Exchange in 2018. The sampling method used in this reseach is purposive sampling. Based on the sampling method used, there were 88 samples. The analytical method used in this study was ordinal logistic regression analysis and simple linear regression analysis. The results of the reseacrh show that political connections affect environmental performance. That means, companies that have political connections tend to have good environmental performance. Similarly, the results of the effect of political connections on profitability show the same. It also means that companies with political connections also have a high level of profitability.